Template Effect of Pd-Pb/CaCO3 Catalyst for Selective Hydrogenation of Phenylacetylene - Li, Changyou; Chi, Ji-an; Guo, Yifei (Asian Journal of Chemistry, 2011)
For investigating effects of support and ageing treatment on the capability of catalyst, conventional impregnation method was used, assist agent such as EDTA, oxalic acid on the capability of Pd- Pb/CaCO3 catalyst for selective hydrogenation of phenylacetylene was investigated. The results showed that calcite, one crystal type of CaCO3, presents obvious template effect in the presence of oxalic acid. In addition, dispersion measurement indicated that ageing treatment can lead to congregation of Pb particles and high selectivity (98.2 %) was also obtained.